Kesehatan Reproduksi Dalam Perspektif Alqur'an (KAJIAN Ayat-Ayat Kebidanan) - Islamiyatur Rokhmah (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
In this research will be studied about reproductive health in the perspective of the Qur’an, the verses that will be discussed thistime include reproduction health verses both biologically and sociologically, which is related to the relationship of family relationships in the family process of reproductive health. The research method used in this study is a literary research that examines the verses of Alqur’an on reproductive health, by looking at various views of contemporary and classical mufassir.